Anatomical and Functional Features of the Internal Rectal Prolapse With Outlet Obstruction Determined With 3D Endorectal Ultrasonography and High‐Resolution Anorectal Manometry: An Observational Case‐Control Study. (August 2018) - Brusciano, Luigi; Tolone, Salvatore; Limongelli, Paolo; Del Genio, Gianmattia; Messina, Federico; Martellucci, Jacopo; Volpe, Mariachiara Lanza; Longo, Antonio; Docimo, Ludovico
Abstract : OBJECTIVES: To investigate correlation between rectal wall thickness (RWT) and anorectal pressures, in obstructed defecation syndrome (ODS) patients caused by internal rectal prolapse. METHODS: ODS patients and healthy volunteers (HVs) underwent 3D endorectal ultrasound (3D‐EUS) and high‐resolution anorectal manometry (HRAM); RWT, total rectal wall volume (TRWV), pushing endorectal pressure (PEP), recto‐anal gradient were determined RESULTS: We enrolled 35 ODS patients and 25 HVs. Patients showed markedly decreased TRWV, PEP, and recto‐anal gradient. Linear correlation was found between markedly reduced TRWV and markedly hypotonic PEP. CONCLUSIONS: HRAM and 3D‐EUS could be performed in ODS assessment, to better understand rectal function.